Blockchain’s Influence on Asset Management and Investment Strategies - Gade, Pavan Kumar; Sridharlakshmi, Narayana Reddy Bommu; Allam, Abhishekar Reddy; Thompson, Christopher Ryan; Venkata, Satya Surya MKLG Gudimetla Naga (Global Disclosure of Economics and Business, 2022)
The merits, drawbacks, and regulatory consequences of blockchain technology on asset management and investing methods are examined in this paper. The study synthesizes literature, case studies, and industry reports using secondary data to assess how blockchain improves portfolio diversification, liquidity, transparency, and risk management. Blockchain allows asset tokenization, enabling fractional ownership and access to varied asset classes, while decentralized markets provide liquidity for illiquid assets. The report states blockchain improves transparency and automates risk management using smart contracts. However, security concerns, operational complexity, and regulatory uncertainty may prevent broad implementation. According to the research, blockchain may be incorporated into asset management processes with a balanced regulatory framework that promotes innovation, security, and compliance. Policymakers should work with industry stakeholders to provide clear blockchain standards that promote advantages and mitigate hazards. This report emphasizes blockchain’s disruptive potential in asset management and recommends innovative approaches to integrate it into established financial institutions.